Impacts of abandoned Gebu Forest escarpment reserve in Kogi State of Nigeria on climate change: need for forest institutional measures (2010)
The study examines abandoned Gebu Forest Escarpment Reserve (GFER) in Kogi State, Nigeria with a view to recommending forest institutional measures for climate change mitigation. The method used for the study was socio-economic survey to gather data through digital mapping, observations, administration of questionnaire and the use of secondary data. The results indicated that the built-up area; mosaic of farmlands/settlements; riparian forest; and wooded savanna within the forest reserve occupy 7.13%, 25.07%, 44.17% and 23.63% respectively. A total of estimated 5,413,216 kg of CO2 is lost to the atmosphere per year in GFER as a result illegal occupation of the community people within the forest reserve. The forest reserve has a composition of trees that are predominantly of savanna species. The respondents (76.67%) were aware of the GFER and majority of the respondents affirmed their livelihood dependency on Gebu forest reserve for farming, grazing, hunting, sales of forest products and collection of fuelwood for energy. The causes of anthropogenic activities of the communities within and around the GFER include absence of forest management by the State Forestry Department; high population growth and unsustainable agricultural practices while the effects of these activities include increase in environmental temperature, flooding, dryness of watershed and droughts. The binary logistic model for institutional measures for climate change mitigation of GFER in Kogi State indicated overall significant fit to the data judging from the chi square value (df, 7 ) =143.62 that is significant at p<0.05. The final loss of the model indicated a value of 7.58. It is recommended that a New Forest Management Plan should be produced for a good tenet of Gebu Forest Escarpment Reserve Management; the Government of Kogi State should enunciate robust forest policy and be complimented with an enactment of forestry act; and secondary forest road should be constructed within and near the forest reserve for easy accessibility, policing, motoring and evaluation of the forest reserve.